‘Vienen de gente de mucha discreción y entendimiento:’ ethnic identity, ambivalence, and colonial discourses in Diego Muñoz Camargo’s Descripción de la ciudad y provincia de Tlaxcala. - Espericueta, José Gabriel (Colonial Latin American Review, 2017)
Diego Muñoz Camargo'sDescripción de la ciudad y provincia de Tlaxcala(1585) is a well-known reference on the history of Tlaxcala that scholars have studied to better understand Tlaxcalan participation in the conquest of Tenochtitlan, its relationship with the Spanish Crown, and the author's selective approach to local history. Often, these approaches present the historian as acculturated or Hispanized because of his celebration of the Spanish or criticism of local religious practices. This article complicates such approaches in order to show the complex ways that the author approached issues of cultural difference. Examining Muñoz Camargo's recourse to colonial discourses of morality, I argue that the author molds and tailors these discourses to fit local Tlaxcalan circumstances. In doing so, I show how he humanizes Tlaxcala's ruling elite while exemplifying the inherent ambivalence of moral authority in Colonial New Spain.